POLA DISTRIBUSI KAYU PENGHARA UNTUK INDUSTRI PENGGERGAJIAN DI DAERAH JAWA TIMUR - Subandi Antaatmadja; Rachman Effendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Logs as raw material of sawmilling industry in East Java are provided by Forest District Administration of Perum Perhutani. Every year Perum Perhutani makes a plan to distribute the raw material for sawmilling industry. Perum Perhutani, in particular Unit Two East Java, has been striving for improving the raw material supplies throught the improvement of quality of teak logs continuity of supply.In determining the distribution pattem of raw materials from forest districts to individual sawmill transportation cost should be one of deciding factors.The aim of this investegation is to find the distribution pattern of transporting the logs from forest districts to individual sawmill so as to minimize the total transportation cost. The results of the investigation are :1.Jatirogo sawmill is the largest supplier of logs while Gresik is the smallest. 2.The minimum total cost of transporting the raw material is Rp 229.314.150,-.